Emotional Regulation Among Single Mother Teachers in Elementary Schools - Septiantika, Dewi Fortuna; Mu’arifah, Alif (Buletin Konseling Inovatif, 2025)
Single mother teachers face great challenges in carrying out dual roles as educators and caregivers, while also handling household chores. This pressure often affects their emotional stability, so that single mother teachers often vent their anger on those around them. The purpose of this research was to determine the description and factors causing single-mother teachers' emotional regulation. Used a qualitative research method with a phenomenological study approach. Used semi-structured interviews and non-participant observation as a data collection method. The subjects in the research were taken using purposive sampling techniques and snowball sampling techniques. The subjects of the research were five single mother teachers aged 30-45 years, working as elementary school teachers (SD) and having children aged 2-13 years. Analysis of the research used content analysis data. The results showed that single mother teacher's emotional regulation involved the process of monitoring, then evaluating, modifying, and re-evaluating emotions because the subjects still had difficulty finding the right regulation strategy, so other factors were needed such as social support, professionalism, religiosity, reducing multitasking, and social comparison. Further research is recommended to conduct longer observations of subject interactions both at school and at home, more in-depth interviews, increase the number of subjects, expand the location and criteria of the subjects, such as single mother teachers at the junior high or high school level who teach at junior high or high school.